Semaphorin3A released from human dental pulp cells inhibits the increase in interleukin‐6 and CXC chemokine ligand 10 production induced by tumor necrosis factor‐α through suppression of nuclear factor‐κB activation. (22nd September 2020) - Shindo, Satoru; Kumagai, Tomoki; Shirawachi, Satomi; Takeda, Katsuhiro; Shiba, Hideki
Abstract: Human dental pulp cells (HDPCs) play an important role in pulpitis. Semaphorin3A (Sema3A), which is an axon guidance molecule, is a member of the secretory semaphorin family. Recently, Sema3A has been reported to be an osteoprotective factor and to be involved in the immune response. However, the role of Sema3A in dental pulp inflammation remains unknown. The aim of this study was to reveal the existence of Sema3A in human dental pulp tissue and the effect of Sema3A which is released from tumor necrosis factor (TNF)‐α‐stimulated HDPCs on production of proinflammatory cytokines, such as interleukin (IL)‐6 and CXC chemokine ligand 10 (CXCL10), from HDPCs stimulated with TNF‐α. Sema3A was detected in inflamed pulp as compared to normal pulp. HDPCs expressed Neuropilin‐1(Nrp1) which is Sema3A receptor. TNF‐α increased the levels of IL‐6 and CXCL10 in HDPCs in time‐dependent manner. Sema3A inhibited production of these two cytokines from TNF‐α‐stimulated HDPCs. TNF‐α induced soluble Sema3A production from HDPCs. Moreover, antibody‐based neutralization of Sema3A further promoted production of IL‐6 and CXCL10 from TNF‐α‐stimulated HDPCs. Sema3A inhibited nuclear factor (NF)‐κB P65 phosphorylation and inhibitor κBα degradation in TNF‐α‐stimulated HDPCs. These results indicated that Sema3A is induced in human dental pulp, and TNF‐α acts on HDPCs to produce Sema3A, which partially inhibits the increase in IL‐6 and CXCL10 production induced by TNF‐α, and that the inhibition leads to suppression of NF‐κB activation. Therefore, it is suggested that Sema3A may regulate inflammation in dental pulp and be novel antiinflammatory target molecule for pulpitis.